Natural Selection of H5N1 Avian Influenza A Viruses with Increased PA-X and NS1 Shutoff Activity - Aitor Nogales (Viruses, 2021)
Influenza A viruses (IAV) can infect a broad range of mammalian and avian species. However, the host innate immune system provides defenses that restrict IAV replication and infection. Likewise, IAV have evolved to develop efficient mechanisms to counteract host antiviral responses to efficiently replicate in their hosts. The IAV PA-X and NS1 non-structural proteins are key virulence factors that modulate innate immune responses and virus pathogenicity during infection. To study the determinants of IAV pathogenicity and their functional co-evolution, we evaluated amino acid differences in the PA-X and NS1 proteins of early (1996–1997) and more recent (since 2016) H5N1 IAV. H5N1 IAV have zoonotic and pandemic potential and represent an important challenge both in poultry farming and human health. The results indicate that amino acid changes occurred over time, affecting the ability of these two non-structural H5N1 IAV proteins to inhibit gene expression and affecting virus pathogenicity. These results highlight the importance to monitor the evolution of these two virulence factors of IAV, which could result in enhanced viral replication and virulence.